Analysis, design and construction of foundations - Cheng, Y. M.; Law, Chi Wai; Liu, Leilei (CRC Press, 2021)
Analysis, Design and Construction of Foundations outlines methods for analysis and design of the construction of shallow and deep foundations with particular reference to case studies in Hong Kong and China, as well as a discussion of the methods used in other countries. It introduces the main approaches used by geotechnical and structural engineers, and the precautions required for planning, design and construction of foundation structures. Some computational methods and computer programmes are reviewed to provide tools for performing a more realistic analysis of foundation systems. The authors examine in depth the methods used for constructing shallow foundations, deep foundations, excavation and lateral support systems, slope stability analysis and construction, and ground monitoring for proper site management. Some new and innovative foundation construction methods are also introduced. It is illustrated with case studies of failures and defects from actual construction projects. Some advanced and modern theories are also covered in this book. This book is more targeted towards the understanding of the basic behavior and the actual construction of many geotechnical works, and this book is not dedicated to any design code or specification, though Euro codes and Hong Kong code are also used in this book for illustration. It is ideal for consulting geotechnical engineers, undergraduate and postgraduate students.